Tindak Pidana Penyalahgunaan Senjata Api dan Senjata Tajam Dalam Undang-Undang Darurat No. 12 tahun 1951 dikaitkan dengan Faktor Korelatif Kriminalisasi - Leonardus Agung Putra Utama; Febby Mutiara Nelson (Faculty of Sharia and Law UIN Syarif Hidayatullah Jakarta, 2022)
The main difference between the Emergency Law 12/1951 and the law that came before it is how punishments work. A sentence of 4 (four) years will be given if someone transfers guns without permission from the Chief of Police in Article 4c and Article 3 of Law 8 of 1948. When it comes to the Emergency Law 12/1951, it is punishable by death, life imprisonment, or a temporary prison sentence of up to twenty years. The difference in punishments is big because of the state's security situation at the time the emergency law was passed. However, do these sanctions still make sense in light of the current situation? People who do this kind of research call it